1. The effect of agri-environment schemes on bees on Shropshire farms. 2. The effect of agri-environment schemes on bumblebee colony success - Crowther, Lucy (2019)
The decline of bees and other invertebrate pollinators is cause for global concern, endangering the stability of ecosystems and economic markets. Modern intensive agriculture has been identified as a key driver causing this decline, through the loss of foraging and nesting habitats and agrochemical applications. Alterations to land management techniques and farming styles through Government-run agri-environment schemes (AES) have the potential to restore the local landscape to benefit wild bees. Bee abundance and species richness were surveyed over a season, along with forage plant usage, on 18 farms in Shropshire (UK) to assess the effectiveness of AES in conserving and restoring local bee communities. Farms were classified into three treatment groups: (i) Conventional (intensive farming with little to no input into “wildlife-friendly” farming actions), (ii) Entry-Level Stewardship AES (ELS: broad, flexible, non-competitive admission), and (iii) Higher-Level Stewardship AES (HLS: strict, high-input options, competitive admission), covering a range of farm types. Bee abundance and species diversity were significantly higher on AES-compliant farms when compared to Conventional farms. AES-compliant farms also showed greater flowering plant diversity used as foraging resources. Small non-significant differences in abundance and species richness were identified between ELS and HLS, with ELS slightly higher in mean species diversity and HLS slightly higher in overall abundance. This study highlights that set-aside of uncultivated field margins, hedgerow restoration, late-cut meadows and the sowing of nectar-rich flower mixes are effective AES options to improve the agricultural landscape for bee communities. Flowering plants currently considered agricultural weeds are important forage resources for bees throughout the season and can benefit local bee communities.